Burden of malaria among adult patients attending general medical outpatient department and HIV care and treatment clinics in Oromia, Ethiopia: a comparative cross-sectional study. (December 2015) - Alemayehu, Guda; Melaku, Zenebe; Abreha, Tesfay; Alemayehu, Bereket; Girma, Samuel; Tadesse, Yehualashet; Gadisa, Tsigereda; Lulseged, Sileshi; Balcha, Taye; Hoos, David; Teka, Hiwot; Reithinger, Richard
Abstract Background Malaria and HIV/AIDS constitute major public health problems in Ethiopia, but the burden associated with malaria-HIV co-infection has not been well documented. In this study, the burden of malaria among HIV positive and HIV negative adult outpatients attending health facilities in Oromia National Regional State, Ethiopia was investigated. Methods A comparative cross-sectional study among HIV-positive patients having routine follow-up visits at HIV care and treatment clinics and HIV-seronegative patients attending the general medical outpatient departments in 12 health facilities during the peak malaria transmission season was conducted from September to November, 2011. A total of 3638 patients (1819 from each group) were enrolled in the study. Provider initiated testing and counseling of HIV was performed for 1831 medical outpatients out of whom 1819 were negative and enrolled into the study. Malaria blood microscopy and hemoglobin testing were performed for all 3638 patients. Data was analyzed using descriptive statistics, Chi square test and multivariate logistic regression. Results Of the 3638 patients enrolled in the study, malaria parasitaemia was detected in 156 (4.3 %); malaria parasitaemia prevalence was 0.7 % (13/1819) among HIV-seropositive patients and 7.9 % (143/1819) among HIV-seronegative patients. Among HIV-seropositive individuals 65.4 % slept under a mosquito bed net the night before data collection, compared to 59.4 % of HIV-seronegative individuals. A significantly higher proportion of HIV-seropositive malaria-negative patients were on co-trimoxazole (CTX) prophylaxis as compared to HIV-malaria co-infected patients: 82 % (1481/1806)versus 46 % (6/13) (P = 0.001). HIV and malaria co-infected patients were less likely to have the classical symptoms of malaria (fever, chills and headache) compared to the HIV-seronegative and malaria positive counterparts. Multivariate logistic regression showed that HIV-seropositive patients who come for routine follow up were less likely to be infected by malaria (OR = 0.23, 95 % CI = 0.09–0.74). Conclusion The study documented lower malaria prevalence among the HIV-seropositive attendants who come for routine follow up. Clinical symptoms of malaria were more pronounced among HIV-seronegative than HIV-seropositive patients. This study also re-affirmed the importance of co-trimoxazole in preventing malaria symptoms and parasitaemia among HIV- positive patients.